Performance analysis, feedback and communication in coaching - O´Donoghue, P.; Mayes, A. (Routledge handbook of sports performance analysis, 2013)
Sports performances arc complex and dynamic situations that yield a potentially large volume of quantitative and qualitative information. Coaches need to identify and act on the most critical information to help players improve. The role of performance analysis within the coaching process is to produce quantitative information allowing areas requiring attention to be quickly identified. This allows coaches to focus on those areas requiring attention and to select video sequences to discuss with players through interactive use of video analysis systems. Coaches and players can then engage in detailed analysis of video sequences, identifying why and how performance can improve and to make decisions about training to enhance performance. The use of information by coaches and how it is communicated to players has evolved as performance analysis technology has developed in recent years.